Extraction, Application and Characterization of Dyed Fabric from Ptericarpus erinaceous - Joshua Yakubu; Bifam Mathias; Andema Aaron Kanadi; Sunday Akuewanhor Osemeahon (African Journal of Sciences and Traditional Medicine, 2026)
Growing environmental and health concerns regarding synthetic dyes have renewed interest in natural colorants for textile applications. This study aimed to extract dye from the stem of Pterocarpus erinaceus, apply it to cotton fabric, and characterize the resulting dyed material. The dye was extracted through maceration, producing a yield of 16%. The extract was initially applied without a mordant and subsequently using pre-mordanting, simultaneous mordanting, and post-mordanting techniques with CuSO₄, KAl(SO₄)₂·12H₂O, and FeSO₄·7H₂O. Post-mordanting produced the most attractive shades, including dark brown, brown, and gray, with dye-absorption values of 0.07, 0.07, and 0.05 for CuSO₄, KAl(SO₄)₂·12H₂O, and FeSO₄·7H₂O, respectively. The dyed fabrics exhibited moderate-to-good color fastness to washing, rubbing, and light, with ratings ranging from 3.0 to 5.0; mordanted samples generally demonstrated superior performance. Scanning electron microscopy and thermogravimetric analysis further indicated a strong relationship between the surface morphology and thermal behavior of the dyed cotton fabrics. These findings demonstrate the potential of P. erinaceus stem extract as a natural dye for cotton textiles and provide a basis for further research evaluating natural mordants as alternatives in sustainable textile coloration.